Uremic Vascular Calcification Is Correlated With Oxidative Elastic Lamina Injury, Contractile Smooth Muscle Cell Loss, Osteogenesis, and Apoptosis: The Human Pathobiological Evidence - Chang, Jia-Feng; Liu, Shih-Hao; Lu, Kuo-Cheng; Ka, Shuk-Man; Hsieh, Chih-Yu; Ho, Chun-Ta; Lin, Wei-Ning; Wen, Li-Li; Liou, Jian-Chiun; Chang, Shu-Wei; Wu, Chang-Chin; Wang, Ting-Ming; et al. (Frontiers in Medicine, 2020)
Background Uremic vascular calcification (UVC) is reminiscent of osteogenesis and apoptosis in vascular smooth muscle cell (VSMC). We aimed to identify how circulating procalcific particles dramatically leak into VSMC layer in human tissue models of vascular rings. Methods According to baseline estimated glomerular filtration rate (eGFR), patients following lower extremity amputation were divided into three groups: normal renal function (eGFR ≧ 60 ml/min), mild-to-moderate (15 ml/min < eGFR ≦ 60 ml/min) and severe chronic kidney disease (CKD) (eGFR ≦ 15 ml/min). Arterial specimens with immunohistochemistry stain were quantitatively analyzed for UVC, internal elastic lamina (EL) disruption, α-SMA, osteogenesis, apoptosis and oxidative injury. Correlations among UVC severity, eGFR, EL disruption, osteogenesis and oxidative injury were investigated. Results CKD arteries were associated with eGFR-dependent EL disruption corresponding to UVC severity. CKD arteries exhibited lower α-SMA, higher expressions of caspase-3 and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL), indicative of contractile VSMC loss and apoptosis. Enhanced expressions of alkaline phosphatase and Runx2 were presented in VSMCs of CKD arteries, indicative of osteogenic differentiation. Above eGFR-dependent UVC and EL disruption correlated expressions of 8-hydroxy-2'-deoxyguanosine (8-OHdG), indicating oxidative EL injury promoted procalcific processes. Conclusions Circulating uremic milieu triggers vascular oxidative stress, leading to progressive internal EL disruption as a key event in disabling VSMC defense mechanisms and catastrophic mineral ion influx into VSMC layer. Oxidative EL injury begins in early CKD, corresponding with active VSMC re-programming, apoptosis, and ultimately irremediable UVC. In light of this, therapeutic strategies targeting oxidative tissue injury might be of vital importance to hinder the progression of UVC related cardiovascular events.